Forensic determination of adulterants in illicit liquor samples by using alcolyzer, densitometer and chemical methods. (2022) - Kumar Verma, Rohit; Kumar Verma, Manoj; Singh Sankhla, Mahipal; Nagar, Varad; Sharma, Anuj; Parihar, Kapil; Guleria, Ankita; Kumar Singh, Gaurav
Abstract: Ingestion of illicit liquor has led to many death cases in India. The use of ethyl alcohol can be done for drinking purposes in an addition it is also used in laboratories. The consumption of illicit liquor shows the symptoms such as confusion, vomiting, nausea, seizure, slow breathing, irregular breathing, hypothermia, inability to stay conscious, lack of physical coordination, etc. due to the overdose of alcohol consumption. The rare ingredients are added depending on the individual's country of alcohol, meanwhile, legitimate quality controls are avoided in the concentration of alcohol and adulteration is recurrent. For Analysis samples of 25 country made seized alcohol and 20 samples of standard alcohol were used and then they were analyzed using the alcolyzer and densitometer instrument. In this research, we are about to find the adulteration in illicit liquor which are harmful to human beings. The results show the percentage of the alcohol and the ethanol and the density of the alcohol which shows the toxicity of the consumption to human health. The density is greater than 1, that alcohol is very poisonous to human health because of adulteration. In this particular research, there is an explanation of various toxic substances added as an adulterant in alcohol that interferes with the human body.